Assessment of anthropometric and dietary iron intake status among young women in university settings - Shilpee Agrawal; Dhrumisha Kanani (World Nutrition, 2025)
Background Iron deficiency and poor nutritional status are prevalent among young women, especially in university settings, due largely to inadequate absorption of dietary iron, increased physiological demands, and lifestyle transitions. In some cases, dietary iron intake may be limited as well. Iron deficiency can have long-term health implications, including anemia, reduced academic performance, and, in young children, impaired physical and cognitive development. Objective This study aimed to assess the nutritional and dietary iron intake of women university students and to explore the relationship between current iron consumption and anthropometric measurements. Methods A cross-sectional study was conducted among 400 female university students aged 19–25 years in Surat, Gujarat, India. Data were collected using a structured questionnaire that included demographic details, and dietary iron intake in the past 24 hours. Anthropometric measurements were also taken. The data were analyzed using SPSS version 25, and Pearson correlation was employed to examine the relationship between dietary iron intake and anthropometric indicators. Results About half of the students (52%) had normal BMI, with 25% underweight and 23% overweight/obese. Most followed a vegetarian diet, frequently skipped meals, and had minimal physical activity. Energy, protein, iron, and vitamin C intakes were below recommendations, while fat intake was high and linked to central obesity. Iron intake inversely correlated with adiposity. Nutrient intake showed no significant association with academic performance. Knowledge and attitudes toward iron nutrition were generally poor. Conclusions Inadequate dietary iron intake was associated with low BMI and anemia, but also adiposity, indicating the need for targeted nutrition education and intervention programs. Regular screening and promotion of iron rich diets complemented with vitamin-C rich foods, especially in institutional settings, are essential to improve both iron levels and overall nutritional status in this vulnerable group.